Mutations Suppressing the Lack of Prepilin Peptidase Provide Insights Into the Maturation of the Major Pilin Protein in Cyanobacteria - Linhartová, Markéta; Skotnicová, Petra; Hakkila, Kaisa; Tichý, Martin; Komenda, Josef; Knoppová, Jana; Gilabert, Joan F.; Guallar, Victor; Tyystjärvi, Taina; Sobotka, Roman (Frontiers in Microbiology, 2021)
Type IV pili are bacterial surface-exposed filaments that are built up by small monomers called pilin proteins. Pilins are synthesized as longer precursors (prepilins), the N terminal signal peptide of which must be removed by the processing protease PilD. A mutant of the cyanobacterium Synechocystis sp. PCC 6803 lacking the PilD protease is not capable of photoautotrophic growth because of the impaired function of Sec translocons. Here, we isolated phototrophic suppressor strains of the original pilD mutant and, by sequencing their genomes, identified secondary mutations in the SigF sigma factor, the γ subunit of RNA polymerase, the signal peptide of major pilin PilA1, and in the pilA1-pilA2 intergenic region. Characterization of suppressor strains suggests that, rather than the total prepilin level in the cell, the presence of non-glycosylated PilA1 prepilin is specifically harmful. We propose that the restricted lateral mobility of the non glycosylated PilA1 prepilin causes its accumulation in the translocon-rich membrane domains, which attenuates the synthesis of membrane proteins.